Hubungan Pengetahuan Dengan Perilaku Personal Hygiene Saat Menstruasi Pada Remaja Putri Di SMK Negeri 1 Sirapit Kabupaten Langkat Tahun 2025 - Tifani Hadi Tri Wahyuni (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Personal hygiene during menstruation is very important to prevent reproductive health disorders. Low knowledge among adolescent girls regarding personal hygiene during menstruation can trigger various health problems. The aim of this study was to determine the relationship between knowledge and personal hygiene behavior during menstruation among female students at SMK Negeri 1 Sirapit. This research used a quantitative design with a cross-sectional approach. A sample of 80 female students was selected from a total population of 100 using Slovin's formula. Data were collected through a questionnaire and analyzed using the Chi-Square test. The results showed that the majority of respondents had low levels of knowledge (48.7%) and poor personal hygiene behavior (57.9%). The Chi-Square test indicated a significant relationship between knowledge and personal hygiene behavior during menstruation (p = 0.014). Good knowledge was associated with good personal hygiene behavior. It is recommended to enhance menstrual hygiene education among adolescent girls.